Protocols for high-speed networks V TC6 WG6.1/6.4 Fifth International Workshop on Protocols for High-Speed Networks (PfHSN '96), 28-30 October 1996, Sophia Antipolis, France - Dabbous, Walid; Diot, Christophe (Chapman & Hall, 1997)
This book presents a state-of-the-art view of transmission control for multimedia applications and new communication system architectures. It focuses on the problems of achieving efficient transmission of multimedia time-constrained application data using high-speed networks and internetworks. Key areas include: protocol development; quality of service issues; protocol analysis; high-performance architectures; implementation of high-speed protocols; experimental studies; application-oriented issues; application-controlled communication systems; protocols for distributed multimedia applications; protocol implementation tools.